Emotional Exhaustion Scale (ECE): Psychometric Properties in a Sample of Portuguese University Students - Ala, Sílvia Maria Fernandes (2024)
Academic emotional exhaustion is the first stage of academic burnout syndrome, and it is necessary to assess it and intervene early, as the consequences can lead to harmful effects on psychological well-being. The main objectives of this study were to explore the psychometric properties of the Emotional Exhaustion Scale (ECE); to assess the association with suffering and positive well-being, using the MHI-5 Inventory; and to provide information on its validity and to compare it with these constructs. A total sample of 526 university students (81% female and 19% male) aged between 17 and 62 (M = 21.42 years and SD = 5.78) took part in this study. Exploratory and confirmatory factor analyses were carried out. In the internal consistency assessment, the ECE was 0.89 and the MHI-5 was 0.81 (Cronbach’s alpha). Exploratory factor analysis was carried out with Varimax rotation and confirmatory analysis, obtaining the factor that explains 50.5% of the variance. The results indicated that the ECE has adequate psychometric properties for use with higher education students in Portugal. Its use by mental health professionals in higher education institutions could be very relevant for screening for emotional exhaustion and thus preventing possible serious pathologies.